2022
DOI: 10.1186/s12885-022-09554-9
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of a prospective, multicenter, phase II clinical trial of safety and efficacy evaluation of long course neoadjuvant chemoradiotherapy plus tislelizumab followed by total mesorectal excision for locally advanced rectal cancer (NCRT-PD1-LARC trial)

Abstract: Background Long course radiotherapy plus neoadjuvant chemotherapy followed by resection (total mesorectal excision, TME) has accepted widespread recognized in the treatment of locally advanced rectal cancer (LARC). Tislelizumab, an anti-PD1 humanized IgG4 monoclonal antibody, has been demonstrated with clinical activity and is approved for treating recurrent/refractory classical Hodgkin lymphoma and locally advanced/metastatic urothelial carcinoma in China. However, the safety and efficacy of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…However, several single-arm clinical trials of neoadjuvant combination therapy, including immunotherapy, are designed to assess clinical outcomes more quickly. [28][29][30] Therefore, there is an urgent need to examine an effective treatment for locally advanced rectal cancer. Based on the convenience of the mrTRG assessment, every patient recruited in this study can reach the primary endpoint in 12 weeks so that we can assess the curative effect of this combination therapy quickly.…”
Section: Discussionmentioning
confidence: 99%
“…However, several single-arm clinical trials of neoadjuvant combination therapy, including immunotherapy, are designed to assess clinical outcomes more quickly. [28][29][30] Therefore, there is an urgent need to examine an effective treatment for locally advanced rectal cancer. Based on the convenience of the mrTRG assessment, every patient recruited in this study can reach the primary endpoint in 12 weeks so that we can assess the curative effect of this combination therapy quickly.…”
Section: Discussionmentioning
confidence: 99%
“…This NCRT-PD1-LARC was a prospective, multicenter, single-arm, phase II trial (Clinical trial number: NCT04911517). The study design was described previously ( 24 ). To allow patient enrollment in accordance with clinical practice, we undertook a protocol amendment to include patients with mid-to-low locally advanced rectal cancer (0-10cm above anal verge) with cT3-4aN0M0 or cT1-4a N1-2M0 pre-staged by MRI.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the PACIFIC-2 aimed to evaluate the benefit of concurrent durvalumab with chemoradiation (NCT03519971). Given these results, we designed this phase II, multicenter, prospective, single-arm trial to evaluate the efficacy and safety of LR-CRT combined with concurrent tislelizumab in patients with LARC ( 24 ). In this manuscript, we will report the interim result of this study.…”
Section: Introductionmentioning
confidence: 99%
“…An American trial reported in 2021 assessed whether the addition of pembrolizumab to neoadjuvant chemoradiotherapy can lead to an improvement in the neoadjuvant rectal (NAR) score instead of pCR compared with 5-fluorouracil, leucovorin, and oxaliplatin (FOLFOX) (77). As shown in Figure 3, the NAR score is calculated according to the following formula as a predictive indicator of survival after preoperative chemoradiotherapy for rectal cancer (78). Patients with stage II/III LARC with distal location (cT 3-4 , ≤ 5 cm from anal verge, N 0-2 ), with bulky disease (any cT 4 or tumor within 3 mm of mesorectal fascia), at high risk for metastatic disease (cN 2 ), and/ or who were not candidates for sphincter-sparing surgery (SSS) were enrolled.…”
Section: Programmed Cell Death 1/ Programmed Cell Death Ligand 1 Inhi...mentioning
confidence: 99%
“…Our center also initiated a prospective, multicenter, phase 2 clinical trial to explore safety and efficacy of long-course neoadjuvant chemoradiotherapy plus tislelizumab followed by TME for LARC (78). As of 30 June 2022, a total number of patients (n = 43) were enrolled, while 30 (29 pMMR/non-MSI-H and 1 dMMR/MSI-H) patients had undergone TME surgery, with the R0 resection rate of 100% and sphincter-saving resection rate of 90.0% (27/30).…”
Section: Exploration Of Neoadjuvant Antiprogrammed Cell Death 1/progr...mentioning
confidence: 99%